Rodinný dům s provozovnou - Žižka, Josef (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Předmětem této bakalářské práce je návrh a projektová dokumentace rodinného domu s provozovnou kadeřnictví v Příměticích. Budova se skládá ze dvou nadzemních a jednoho podzemního podlaží. Zastřešený sedlovou střechou. Nosný systém je navržen v systému Porotherm. Kromě vlastního projektu je součástí práce i architektonická studie a seminární práce.

The subject of this bachelor´s thesis is to design and project family house with the place for business, which will be used as a hairdressing salon. The building consists of two floors and one underground floor, which is covered with saddled roof. The supporting structure is designed on the base of system Porotherm. This thesis also includes part with architectural study and seminar work.
Family house with establishment
Keywords: Rodinný dům s provozovnou; kadeřnictví; suterén; nadzemní podlaží; plochá střecha; příhradový vazník; projektová dokumentace; House of establishment; hairdresser; basement; ground floor; flat roof; trusses; project documentation